Impact of Socioeconomic Status on Clinical Outcomes in Patients With ST-Segment–Elevation Myocardial Infarction. Issue 1 (January 2019) - Biswas, Sinjini; Andrianopoulos, Nick; Duffy, Stephen J.; Lefkovits, Jeffrey; Brennan, Angela; Walton, Antony; Chan, William; Noaman, Samer; Shaw, James A.; Ajani, Andrew; Clark, David J.; Freeman, Melanie; et al.
Abstract : Background: Low socioeconomic status (SES) has been previously shown to be associated with worse cardiovascular outcomes. However, unlike in Australia, many of these studies have been performed in countries without universal healthcare where SES may be expected to have a greater impact on care and outcomes. We sought to determine whether there is an association between SES and baseline characteristics, clinical outcomes and use of secondary prevention therapy in patients with ST-segment–elevation myocardial infarction undergoing percutaneous coronary intervention (PCI). Methods and Results: We prospectively collected data on 5665 consecutive ST-segment–elevation myocardial infarction PCI patients between 2005 and 2015 from 6 government-funded hospitals participating in a multicenter registry. Patients were categorized into SES quintiles using the Index of Relative Socioeconomic Disadvantage system, a score allocated to each residential postcode based on factors like income, educational level, and employment status by the Australian Bureau of Statistics. In our study, lower SES patients were more likely to have diabetes mellitus, smoke, and initially present to a non-PCI capable hospital (all P ⩽0.01). Among primary PCI patients, the median time to reperfusion was slightly higher in lower SES groups (211 [144–337] versus 193 [145–285] minutes, P <0.001). Drug-eluting stent use was higher in the higher SES groups ( P <0.001). At 12 months after PCI, lower SES patients had higher rates of ongoing smoking and lower use of guideline-recommended secondary prevention therapy (both P <0.01). Despite these differences, SES group was not found to be an independent predictor of 12-month major adverse cardiovascular events. Conclusions: Lower SES patients have more comorbidities and experienced slightly longer reperfusion times but otherwise similar care. Despite these baseline differences, clinical outcomes after ST-segment–elevation myocardial infarction PCI were similar regardless of SES. Abstract : Supplemental Digital Content is available in the text.